2022
DOI: 10.3390/catal13010040
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silicotungstic Acid/Ni-Zr-O Composite Nanoparticle by Using Bimetallic Ni-Zr MOF for Fatty Acid Esterification

Abstract: In this study, the bimetallic Ni-Zr MOF-derived nickel-zirconium oxide (Ni-Zr-O)-impregnated silicotungstic acid (HSiW) nanocomposite catalyst (HSiW@Ni-Zr-O) was prepared via a hydrothermal procedure followed by a pyrolysis treatment, and its structural, morphological, and surface components and oxidation states were characterized by using XRD, FTIR, TPD-NH3, SEM, TEM, N2 physisorption, and XPS analyses. Then, the nanocomposite catalysts were successfully applied to the esterification of oleic acid (OA) with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…It was shown that use of electrostatic coagulation yielded significant reductions in the time required to fully separate the biodiesel and glycerin, as compared to gravitational settling. Gashaw and Teshita (2014) demonstrated that transesterification of oils having higher free fatty acid content was difficult when an alkaline base catalyst was used, and this often resulted in soap formation (Huang et al, 2023), used transesterification with an in situ extraction of product to produce a more efficient biodiesel yield (Mahmoodi et al, 2019;Zhang et al, 2022). Acknowledged the need for esterification/transesterification of FFA for different oils using heterogenous or homogenous catalysis.…”
Section: Literature Searchmentioning
confidence: 99%
“…It was shown that use of electrostatic coagulation yielded significant reductions in the time required to fully separate the biodiesel and glycerin, as compared to gravitational settling. Gashaw and Teshita (2014) demonstrated that transesterification of oils having higher free fatty acid content was difficult when an alkaline base catalyst was used, and this often resulted in soap formation (Huang et al, 2023), used transesterification with an in situ extraction of product to produce a more efficient biodiesel yield (Mahmoodi et al, 2019;Zhang et al, 2022). Acknowledged the need for esterification/transesterification of FFA for different oils using heterogenous or homogenous catalysis.…”
Section: Literature Searchmentioning
confidence: 99%
“…In general, biodiesel is derived by esterification/transesterification of free fatty acids (FFAs), plant oils, animal fats, waste cooking oils, and microalgae and triglyceride with short-chain alcohols in the presence of homogeneous/heterogeneous catalysts [5]. Although the usage of homogeneous catalysts can achieve a high percentage of conversion rates, it also causes some salient problems such as expensive separation stages and large amounts of chemical wastewater [6]. Therefore, heterogeneous catalysts have just been developed for various applications due to their less hazardous, ease of separation, and recyclability [7][8][9].…”
Section: Introductionmentioning
confidence: 99%